Effect of anchoring groups on the electronic transport properties of biphenyl and phenyl-pyridine molecules - G.R. Berdiyorov (7170563) (2021)
Single-molecule quantum transport calculations are performed using nonequilibrium Green's functional formalism for biphenyl and phenyl-pyridine molecules asymmetrically anchored to gold electrodes via different edge groups. Clear current rectification is obtained depending on the edge group of the molecules with rectification level up to 4. Among the considered 6 structures, 4-mercaptophenyl-2,6-dithiolpyridine and 4′-mercaptomethyl-4-thiol-biphenyl molecules show the best diode parameters such as asymmetry, nonlinearity and responsivity, originating from bias-dependent charge localization in the systems as revealed in detailed analysis of the transmission eigenvalues and molecular projected self-consistent Hamiltonian states. The obtained results can be useful in developing molecular electronics devices, such as molecular diodes. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2021.02.078